Female Sex Work and HIV Risks in Croatia - Štulhofer, Aleksandar; Drglin, Tihana; Puljiz, Mario; Miklin, Marko; Baćak, Valerio (2009)
The aim of this paper was to analyze and compare the prevalence of HIV-related sexual risk taking among Croatian female sex workers (FSW) in two major urban areas. Two groups of FSWs were interviewed in Zagreb (n=65) and Split (n=89). Participants’ mean age was 33.3 (SD=8.32). Interviews were conducted by outreach organizations that provide health services to sex workers in the two cities. The study used a brief questionnaire with standardized behavioral and HIV knowledge indicators. The two groups of FSWs differed significantly in most sociodemographic and socio-sexual indicators. Women from the Split sample were somewhat younger (χ 2=6.87, p<.05), less educated (χ 2=7.71, p<.05), less likely to be single (χ 2=19.81, p<.001), and less likely to be unemployed (χ 2=5.22, p<.05). Also, they injected drugs in higher proportion (χ 2=35.03, p<.001), but had less clients in the preceding month (χ 2=12.54, p<.001) and were less likely to be abused by them (χ 2=7.18, p<.01). HIV testing was significantly more prevalent among participants in the Split sample (χ 2=4.95, p<.05). In multivariate analysis, selling sex in Zagreb (OR=14.48, p<.01), having secondary or higher education (OR=4.76, p<.05), ever tested for HIV (OR=8.34, p<.05), and having assessed the risk of getting infected with HIV as high (OR=.23, p<.05) were significantly associated with consistent condom use with clients in the last month. The findings of this first systematic study on HIV-related risks among FSWs in Croatia point to the need to update targeted intervention programs by improving the prevention of HIV risks associated with injecting drug use (Split) and by a more efficient HIV educational approach.
Projekt MZOS
ENG